Polymorphs, salts, and cocrystals: what's in a name? - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)
The December 2011 release of a draft United States Food and Drug Administration (FDA) guidance concerning regulatory classification of pharmaceutical cocrystals of active pharmaceutical ingredients (APIs) addressed two matters of topical interest to the crystal engineering and pharmaceutical science communities: (1) a proposed definition of cocrystals; (2) a proposed classification of pharmaceutical cocrystals as dissociable ``API-excipient'' molecular complexes. The Indo U.S. Bilateral Meeting sponsored by the Indo-U.S. Science and Technology Forum titled The Evolving Role of Solid State Chemistry in Pharmaceutical Science was held in Manesar near Delhi, India, from February 2-4, 2012. A session of the meeting was devoted to discussion of the FDA guidance draft. The debate generated strong consensus on the need to define cocrystals more broadly and to classify them like salts. It was also concluded that the diversity of API crystal forms makes it difficult to classify solid forms into three categories that are mutually exclusive. This perspective summarizes the discussion in the Indo-U.S. Bilateral Meeting and includes contributions from researchers who were not participants in the meeting.

Polymorphs, salts and cocrystals: what's in a name? (vol 12, pg 2147, 2012) - Aitipamula, Srinivasulu; Banerjee, Rahul; Bansal, Arvind K.; Biradha, Kumar; Cheney, Miranda L.; Choudhury, Angshuman Roy; Desiraju, Gautam R.; Dikundwar, Amol G.; Dubey, Ritesh; Duggirala, Nagakiran; Ghogale, Preetam P.; Ghosh, Soumyajit; et al. (Crystal Growth & Design, 2012)

Synthesis, crystal structures, dielectric and magnetic properties of manganese sulfonyldibenzoates - Balendra; Singh, Bharti; Banday, Azeem; Tewari, Shailabh; Kumar, Vineet; Murugavel, Sevi; Joy, P. A.; Ramanan, Arunachalam (Crystengcomm, 2021)
{A systematic investigation of the system manganese(II) salt-H(2)SBA-auxiliary ligand-solvent successfully led to the isolation of six new multidimensional coordination polymers: [Mn-5(2-pic)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (1), [Mn-3(pyzc)(2)(DMF)(H2O)(SBA)(2)]center dot DMF center dot H2O (2), [Mn-5(pyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (3), [Mn-5(mpyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (4), [Mn-2(phen)(2)(H2O)(SBA)(2)]center dot 2DMA (5) and [Mn-3(phen)(2)(SBA)(3)]center dot 5DMF (6), where SBA = 4,4'-sulfonyldibenzoate 2-pic = 2-picolinate